Bending collapse of dual rectangle thin-walled tubes for conceptual design. (February 2019) - Bai, Jiantao; Meng, Guangwei; Wu, Hong; Zuo, Wenjie
Abstract: In engineering, the bending deformations of thin-walled tubes mostly are under three-point loading. However, for the dual rectangle thin-walled tube (DRTWT), the theoretical prediction of the three-point bending collapse is still an unsolved problem. In this paper, the three-point bending collapse of the DRTWT is innovatively investigated using theoretical prediction and experimental verification. The global energy equilibrium theory is applied to derive the bending characteristic of the DRTWT. It is assumed that all the bending energy is absorbed and distributed along the hinge lines and in the toroidal surfaces during the bending collapse. The analytical results show good agreement with the experimental results. Finally, a simplified bumper structure of automobile is created by using beam elements and spring elements with the derived bending characteristics, which can effectively replace the detailed finite element model (FEM) to accelerate the crashworthiness design of automotive structure at the conceptual design stage. Highlights: The bending collapse of the dual rectangular thin-walled tubes is investigated under three-point bending. The global energy equilibrium theory is applied to derive the bending collapse characteristics. The analytical results show good agreement with the experimental results. The simplified finite element model can accelerate crashworthiness design at the conceptual design phase.